1999
DOI: 10.1590/s0103-84781999000200018
|View full text |Cite
|
Sign up to set email alerts
|

Contração de feridas após cobertura com substitutos temporários de pele

Abstract: Feridas experimentais foram recobertas com substitutos temporários de pele produzidos com poliuretano, hidrocolóide, hemicelulose e vaselina e com gaze, para avaliação do cálculo da área e percentual de contração ao 7º, 14 e 28º dias de evolução. O curativo hidrocolóide proporcionou uma redução da área inicial ao sétimo dia, não se observando diferenças significativa entre os tratamentos nos períodos seguintes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
5
0
5
Order By: Relevance
“…The burn healing occurs by second intention, which is a slow process with high risk of infection, producing scar retraction, which depending on the area of injury can cause extensive scarring and consequently high cost in treatment [ 31 ]. The contraction of skin lesions occurs centripetally fromthe injury edges being caused by the action of myofibroblasts present at the site.…”
Section: Resultsmentioning
confidence: 99%
“…The burn healing occurs by second intention, which is a slow process with high risk of infection, producing scar retraction, which depending on the area of injury can cause extensive scarring and consequently high cost in treatment [ 31 ]. The contraction of skin lesions occurs centripetally fromthe injury edges being caused by the action of myofibroblasts present at the site.…”
Section: Resultsmentioning
confidence: 99%
“…In both groups, there was a gradual reduction in the wound areas from the 7 th DPO. COELHO et al, (1999) and MARTINS et al (2013) also observed an increase in the areas of the wounds in the initial phase of the healing process, caused by the shrinkage of the rim of the lesions due to the action of the lines of tension (Langer Lines). In making the square wounds, the skin was incised in both directions, longitudinal and transversal, determining the increase in area due to stretching caused by the transverse incisions according to Langer's lines (ALGOWER, 1977apud COELHO et al, 1999.…”
Section: Lucas Et Almentioning
confidence: 93%
“…Wound contraction is frequently assessed in these experiments because it allows for a better understanding of the healing process evolution and the maturation of the scar, which represent myofibroblast activity, and the buildup and maturation of collagen fibers (COELHO et al, 1999). Morphometric evaluation assays are employed to measure the diameter of the lesion, in order to establish a comparison of the initial measurement and subsequent results throughout the healing process (LIMA et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This process is favored where the skin is looser, such as the abdomen and trunk (COELHO; REZENDE, TENÓRIO, 1999). Wound contraction is one of the most important aspects when assessing the healing process of open skin wounds (MEDRANO, 2010), and several methods and tools are used to measure the evolution of this phenomenon in wound healing assays (FALCÃO et al, 2001).…”
Section: Introductionmentioning
confidence: 99%